Estudo da associação entre os níveis séricos de interleucina 33 e do receptor solúvel ST2 e a presença de aterosclerose subclínica em pacientes com artrite reumatoide - Maria Raquel da Costa Pinto (2014)
Introduction Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease, which comprises inflammation of the synovia, resulting in peripheral polyarthritis. Apart from presenting great potential for articular damage, RA is also an independent risk factor for early cardiovascular disease (CVD) and mortality. Traditional risk factors and also inflammation inherent to the disease are implicated in endothelial dysfunction and cardiovascular events in RA. Interleukin 33 (IL-33) is a cytokine related to amplification of the articular inflammation, in animal models. Elevated IL-33 serum levels have been described in RA patients, suggesting a possible participation of this cytokine in the physiopathology of the disease. The role of IL-33 in cardiovascular events is also under investigation and it seems that this cytokine has a protective effect in the development of atherosclerosis. Objective To verify the association of the serum levels of IL-33 and its soluble receptor (sST2) with the presence of carotid subclinical atherosclerosis, evaluated by ultrasonography, in a group of RA patients. Methods Cross-sectional observational study in RA patients, free from atherosclerotic CVD. The patients were submitted to clinical evaluation, physical exam and blood sample collection. The General Cardiovascular Risk Score (Framingham) was calculated. Carotid highresolution ultrasonography evaluated the presence of atherosclerotic plaques and the intimamedia thickness (IMT) of common carotid artery wall. IL-33 and sST2 serum levels were measured by ELISA. Results 102 patients were included, 92,5% women, with mean (±SD) age of 55,5 (±10) years old and mean disease duration of 17,6 (±9,5) years. Eighty-four (82,4%) patients had seropositive RA. The traditional cardiovascular risk factors prevalence were: 11,8% of smoking, 16,7% of diabetes, 17,6% history of premature CVD in first degree relatives, 52% of metabolic syndrome, 58,8% of hypertension, 63,7% of dyslipidaemia and 90% of central obesity. The prevalence of carotid plaque was 23,5% and the median of IMT was 0,7 (0,6 0,8) mm. Common carotid IMT and duration of RA were independent factors associated with the presence of plaque. An increase of 0,1 mm in IMT increased by 5,3 times the chance of plaque (CI95%: 2,88 983,37) and each additional year of RA duration increased by 6% the chance of plaque presence (IC95%: 1,01 1,12). Age, cardiovascular risk score and current methotrexate (MTX) use were independent factors associated with IMT. Each additional year of age and each additional unit in cardiovascular risk score increased by 0,003 mm and 0,012 mm, respectively the IMT (CI95%: 0 0,007 and 0,007 0,016). On the other hand, MTX use was associated with a reduction of 0,07 mm in IMT (CI95%: -0,117 -0,013). Sixty-eight (66,7%) patients had IL-33 serum levels above the detection limit with a median value of 69,1 (31,6 114,5) pg/mL. The median sST2 serum level was 469,8 (336,3 651) pg/mL. There was not association between IL-33 or sST2 serum levels and presence of plaque or IMT. Conclusions IL-33 and sST2 serum levels were not associated with subclinical atherosclerosis, estimated by IMT measurement and search of carotid plaques, in this group of established RA patients. Traditional risk factors for atherosclerosis (age and cardiovascular risk score) and disease duration were associated with IMT and presence of plaque, while MTX was related to smaller intima-media thickness.